Research on critical SNR and power allocation of artificial noise assisted secure transmission - Hao DENG; Huiming WANG (Tongxin xuebao)
A comprehensive performance analysis of artificial noise (AN) assisted secure transmission in multiple-input single-output (MISO) wiretap channels was presented.It was shown that the AN scheme did not always improve the security,and provided an exact signal-to-noise ratio (SNR) threshold below which AN did not work.An explicit result of the optimal power allocation (OPA) using the lower bound to the ergodic secrecy rate (ESR) was presented and the OPA for the worst case without the knowledge of the eavesdropper’s relative distance was also provided.Simulations demonstrate that the proposed power allocation result achieves a higher ESR than the equal one.